Assisted technology in Parkinson's disease gait: what's up? - Tamine T. C. Capato; Janini Chen; Johnny de Araújo Miranda; Hsin Fen Chien (Arquivos de Neuro-Psiquiatria)
Background Gait disturbances are prevalent and debilitating symptoms, diminishing mobility and quality of life for Parkinson's disease (PD) individuals. While traditional treatments offer partial relief, there is a growing interest in alternative interventions to address this challenge. Recently, a remarkable surge in assisted technology (AT) development was witnessed to aid individuals with PD.